Butaphosphan and Cyanocobalamin Supplementation in Semen Extender on Chilled Boar Sperm Quality and Life Span - Suwimonteerabutr, J.; Chumsri, S.; Tummaruk, P.; Nuntapaitoon, Morakot (Frontiers in Veterinary Science, 2020)
The objective was to determine the effect of butaphosphan and cyanocobalamin supplementation in semen extender on chilled boar sperm quality and lifetime. A total of 35 ejaculates of boar semen were included. The semen was diluted with Beltsville thawing solution extender supplemented with different concentrations of butaphosphan and cyanocobalamin (0 (control), 0.1, 0.2, 0.3, 0.4 and 0.5%) in the diluted semen. The semen samples were evaluated using a computer assisted sperm analysis system to determine sperm motility and sperm kinetic parameters (i.e., the curvilinear velocity, VCL; straight line velocity, VSL; average path velocity, VAP; linearity, LIN; straightness, STR; amplitude of lateral head , ALH; wobble, WOB and beat cross frequency, BCF). Additionally, sperm viability, acrosome integrity, mitochondrial activity and plasma membrane integrity were evaluated after 4 h (Day 0), 72 (Day 3), 120 (Day 5) and 168 (Day 7) h of storage using SYBR-14-EthD-1, EthD-1, JC-1 and short hypo-osmotic swelling test, respectively. The analyses were carried out by using general linear mixed model (MIXED) procedure of SAS. The statistical models for each data set included group, day after storage and interaction between group and day after storage. The boar was included as a random effect. On day 0 after storage, progressive motility, VCL, VSL, VAP and plasma membrane integrity of boar sperm in 0.3% of butaphosphan and cyanocobalamine supplementation was greater than in 0.4% and 0.5% groups (P<0.05). On day 3 after storage, total motility and progressive motility, VCL, VSL, VAP, LIN, WOB, BCF and plasma membrane integrity in 0.3% was significantly greater than in the control group (P<0.05). The total motility and progressive motility, VAP and WOB in 0.3% of butaphosphan and cyanocobalamine supplementation was greater than the control group in day 5 after storage (P<0.05). However, the motility and progressive motility and the values for all sperm kinetic parameters except ALH in 0.3% of butaphosphan and cyanocobalamine supplementation were greater than the control group in day 7 after storage (P<0.05). In conclusion, 0.3% of butaphosphan and cyanocobalamin supplementation in semen extender improved sperm motility, sperm activity, morphology and lifetime in chilled boar sperm.